Exporting to Canada : a handbook (The Office OttawaCA, 1994)
Provides an economic and market overview; an import summary; information of the Canadian trade regulatory system; and, information on specific import regulations. Looks at business in Canada's market economy; marketing products in Canada; and, provides key steps to successful exporting.
Keywords: MANUALS